1985
DOI: 10.1111/j.1439-0434.1985.tb00821.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sugars and Phenols in Charcoalrot Resistance of Sorghum

Abstract: Total sugars, reducing sugars, and phenols were estimated in internodes of tolerant and highly susceptible sovhum genotypes to charcoal, ln tolerant genotypes the sugar level was 2 to 3 times higher than in susceptible ones; phenol concentration also was higher in tolerant genotypes. In tolerant genotypes, sugar and phenol concentration was high in the lower most and in the upper most mternode. This may be used to identify sources of resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
1
3
0
1
Order By: Relevance
“…The current findings of more total soluble sugar in resistant genotypes compared to susceptible genotypes agreed with Patil et al (1985) [41] , who reported that the decrease in sugar quantity in susceptible genotypes may be attributed to fungus utilisation for growth. Gopalakrishnan et al (2010) [16] observed that 28 percent reduction in the total sugar content of rice seeds due to Sarocladium oryzae infection in susceptible varieties whereas it was 17 percent in resistant varieties.…”
Section: Estimation Of Total and Reducing Sugarssupporting
confidence: 91%
“…The current findings of more total soluble sugar in resistant genotypes compared to susceptible genotypes agreed with Patil et al (1985) [41] , who reported that the decrease in sugar quantity in susceptible genotypes may be attributed to fungus utilisation for growth. Gopalakrishnan et al (2010) [16] observed that 28 percent reduction in the total sugar content of rice seeds due to Sarocladium oryzae infection in susceptible varieties whereas it was 17 percent in resistant varieties.…”
Section: Estimation Of Total and Reducing Sugarssupporting
confidence: 91%
“…Like Fusarium spp., M. phaseolina has been categorized as a weak parasite and requires the senescence of plant cells resulting from stressful environmental conditions or the depletion of nutrients to parasitize the plant (Dhingra et al, 1976). Patil et al (1985) reported that the concentration of carbohydrates in sorghum lines susceptible to M. phaseolina was lower than that of tolerant sorghum lines. It is possible that the results observed in our present study could be explained by this photosynthetic stress-translocation balance theory (Dodd, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…According to Shahabuddhin and Anwar (1992) there was a decrease in total sugar and reducing sugar in jute following inoculation with M. phaseolina. Patil et al (1985) reported that in tolerant genotypes the sugar level was two to three times higher than the susceptible ones. Total phenol content: The total phenol content was found to be higher in the resistant genotype followed by the moderately resistant ones and increased upon inoculation with the pathogen (Table 2).…”
Section: Resultsmentioning
confidence: 99%